PENGARUH KEPERCAYAAN DIRI TERHADAP HASIL BELAJAR MATEMATIKA - Amanda, Salsabilah Dwi; Fahrunnisa, Tiara; Mardiati, Mardiati (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2024)
In this research, the aim is to determine the effect of self-confidence on student exam results. The type of research used is ex post quantitative. The sample in this research was class XII students. Data collection techniques use questionnaires and semester MID exam results. From the results of the analysis carried out using the ex post facto method, it can be seen that there is a relevant influence on self-confidence regarding the results of the class XII mathematics exam at Delisha Private Vocational School. This can be seen from the results obtained with the value = 2.624 > = 2.100 (significance level 0.017). Based on this explanation, it is hoped that students can have self-confidence and positive study habits, as well as improve their learning outcomes. Furthermore, teachers are expected to make learning more enjoyable than before.